2022
DOI: 10.3390/md21010038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Marine Polyketide Plocabulin on Tumor Progression

Abstract: Marine sponges represent one of the richest sources of natural marine compounds with anticancer potential. Plocabulin (PM060184), a polyketide originally isolated from the sponge Lithoplocamia lithistoides, elicits its main anticancer properties binding tubulin, which still represents one of the most important targets for anticancer drugs. Plocabulin showed potent antitumor activity, in both in vitro and in vivo models of different types of cancers, mediated not only by its antitubulin activity, but also by it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Numerous studies have indicated the important role of natural products in the oncological area [ 5 , 6 ]. In particular, several natural compounds have been found to target tumor-angiogenesis-associated cytokines, and apoptotic signaling pathways, such as curcumin, artemisinin, epigallocatechin gallate, resveratrol, emodin, celastrol, thymoquinone, plocabulin, and tocotrienols, have all shown prominent anti-angiogenic effects in the preclinical models of tumor angiogenesis [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated the important role of natural products in the oncological area [ 5 , 6 ]. In particular, several natural compounds have been found to target tumor-angiogenesis-associated cytokines, and apoptotic signaling pathways, such as curcumin, artemisinin, epigallocatechin gallate, resveratrol, emodin, celastrol, thymoquinone, plocabulin, and tocotrienols, have all shown prominent anti-angiogenic effects in the preclinical models of tumor angiogenesis [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mar. Drugs 2023, 21, 307 2 of curcumin, artemisinin, epigallocatechin gallate, resveratrol, emodin, celastrol, thymoqu none, plocabulin, and tocotrienols, have all shown prominent anti-angiogenic effects the preclinical models of tumor angiogenesis [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%